An Armadillo‐Like Flexible Thermal Protection System for Inflatable Decelerators: A Novel Paradigm. Issue 3 (17th September 2013) - Natali, Maurizio; Rallini, Marco; Puglia, Debora; Kenny, Josè; Torre, Luigi
<x xml:space="preserve">Abstract</x> Polymeric ablative materials play a strategic role in the whole aerospace industry: they are used to produce the thermal protection system (TPS), which protects vehicles during the hypersonic flight through a planetary atmosphere. To date, TPSs are typically designed as rigid monolithic heat shields. Inflatable deployable aeroshells (IDAs) offer an alternative to rigid TPSs: IDAs are based on the use of flexible TPSs (FTPSs). State of the art FTPSs can handle heat fluxes up to approximately 20 W cm−2. However, next generation FTPSs for IADs should be able to survive heat fluxes up to 150 W cm−2. To satisfy these stringent requirements, we propose a radically brand‐new paradigm of flexible TPS based on the use of state of the art elastomeric ablatives (EPDM/Aramid) employed to produce the insulation liners for solid rocket motors. This class of ablatives is able to survive heat fluxes in the range of (300–1000) W cm−2. Most important, we envisioned to introduce an "Armadillo‐Like" design in which a series of overlapping sacrificial movable tiles could work as a continuous flexible thermal barrier.<inline-graphic xlink:href="ark:/27927/pgg4svkkwq9" content-type="mame201300267-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />